2021
DOI: 10.3390/nu13082841
|View full text |Cite
|
Sign up to set email alerts
|

Fenton vs. Intergrowth-21st: Postnatal Growth Assessment and Prediction of Neurodevelopment in Preterm Infants

Abstract: Although the survival rate of preterm infants has improved over the years, growth failure and associated impaired neurodevelopmental outcome remains a significant morbidity. Optimal nutrition plays an important role in achieving adequate postnatal growth. Accurate growth monitoring of preterm infants is critical in guiding nutritional protocols. Currently, there is no consensus regarding which growth assessment tool is suitable for monitoring postnatal growth of preterm infants to foster optimal neurodevelopme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 33 publications
2
15
1
Order By: Relevance
“…The studies conducted by Tuzun et al, [11] Reddy et al, [12] Yitayew et al [13] and Patel et al [14] found that there was significant difference in identifying the EUGR rates by both growth charts, contrary to our study, in which we found no statistical difference. The reason for this contradiction could be due to the difference in sample size used, feeding strategy in our unit, which follows a restricted feeding during the period of illness and also we had a higher number of mature infants compared to other studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The studies conducted by Tuzun et al, [11] Reddy et al, [12] Yitayew et al [13] and Patel et al [14] found that there was significant difference in identifying the EUGR rates by both growth charts, contrary to our study, in which we found no statistical difference. The reason for this contradiction could be due to the difference in sample size used, feeding strategy in our unit, which follows a restricted feeding during the period of illness and also we had a higher number of mature infants compared to other studies.…”
Section: Discussioncontrasting
confidence: 99%
“…In a study conducted by Yitayew et al [13] in infants born between 24-33 weeks of gestation, the authors also found that the SGA rate identified by Intergrowth-21st was high but not significant, and the EUGR rate identified was low when compared to Fenton growth charts which was found to be statistically significant. These results were similar to our study except for the statistical significance.…”
Section: Discussionmentioning
confidence: 93%
“…On the contrary, in another study, Reddy et al pointed out that neonates classified as SGA at birth by INTERGROWTH-21st and not by Fenton2013 growth charts had a higher incidence of morbidities such as sepsis and ROP [41]. In other studies, no significant difference was observed for the classification of birth weight for GA in preterm neonates born before 33 weeks between the two assessment growth charts [42,43]. It is very essential to accurately define SGA with appropriate charts, since being born SGA is associated with an increased risk of higher mortality, postnatal growth failure, and neurodevelopmental impairment at 18-22 months of corrected age [44].…”
Section: Discussionmentioning
confidence: 91%
“…The extrauterine environment presents a completely different context for preterm babies, exposing them to unique metabolic responses and morbidities, which contrast significantly with the conditions experienced by fetuses in utero. A retrospective study published in 2021 presented a lower percentage of EUGR with respect to weight and length at discharge when INTERGROWTH-21st curves were used, compared to Fenton2013 curves, and this was associated with poorer language development assessed either at 12 or 24 months [43]. It is important to note that the main limitation of the INTERGROWTH-21st preterm postnatal standards is the limited number of infants born before 33 weeks' gestation who contributed to the development of the growth curves, which potentially affects the validity of the standards.…”
Section: Discussionmentioning
confidence: 99%
“…Parenteral and enteral nutritional support for newborns is based on continuous nutrition guidelines [ 2 – 4 ], and the risk of postnatal growth failure (PGF) in preterm infants remains high [ 5 , 6 ]. Moreover, PGF is associated with subsequent poor neurodevelopment outcomes [ 7 ]. Therefore, the prevention of PGF in preterm infants remains a challenge for physicians.…”
Section: Introductionmentioning
confidence: 99%